HALAL TOURISM IN INDONESIA (CASE STUDY OF DOMESTIC TOURISTS) - Aula Nurul Ma'rifah; M Nasor; Erike Anggraeni (Universitas Muhammadiyah Prof Dr Hamka, 2020)
In increasingly global development, the business climate is always growing. Likewise in the tourism business or the tourism industry. Halal tourism has emerged as a new concept in tourism. Halal tourism is tourism with a concept to facilitate Muslims to worship and avoid non-halal activities on their tour. However, halal tourism is not solely exclusive to Muslims but is open to all communities regardless of religious background. The concept is an opportunity, including Indonesia, which has a Muslim majority population. This study aimed to examine how the views of domestic tourists in Indonesia regarding halal tourism. The population in this study was the number of tourists traveling with pure tourism during the 2018 period of 130.008.566. While the samples of this study were taken by using the Slovin technique with a 5% margin error so that the sample in this study was 400 samples. The data collection technique was conducted by using primary data with written interviews with Indonesian residents who have traveled more than 2 times a year. The results of this study showed that most respondents representing domestic tourists in Indonesia gave positive responses related to the concept of halal tourism and the application of halal tourism in Indonesia. Tourists assume that halal tourism will not be an obstacle to national tourism. Moreover, this concept will be able to provide Muslim and non-Muslim comfort simultaneously. Keywords: Halal Tourism, Indonesia